Przestępstwa przeciwko zrzeszeniom prawa publicznego w projekcie kodeksu karnego Komisji Kodyfikacyjnej Rzeczypospolitej Polskiej - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article examines the work in the criminal law section of the Codifi cation Commission of the Republic of Poland on the construction of the factual circumstances of off ences against public law associations. The analysis is based on the papers delivered during a meeting of the section by Wacław Makowski and Juliusz Makarewicz. The proposals presented in them were used in the fi nal version of Chapter XIX of the draft Polish Criminal Code. The author demonstrates that the construction of the off ences in question was shaped by in-depth discussions within the criminal law section. Their objective was to create a modern form of protection of public law associations in the Criminal Code.
Keywords: Komisja Kodyfikacyjna Rzeczypospolitej Polskiej; Makarewicz Juliusz (1872-1955); projekt kodeksu karnego; zrzeszenia prawa publicznego